تأثير استخدام نموذج التعليم التعاوني فرق تقسيم إنجاز الطلاب في تعليم علم النحو بكتاب متن الأجرومية لدى طلاب معهد الحاج عبد الكريم شعيب جوجوك رانده آجام - Faramila, Gusmila; Dewi, Yelfi; Husni, Arman; Anas, Al-baihaqi (YASIN, 2025)
One of the problems is that the teacher used the tradisional model and did not use the STAD type cooperative education model in teaching grammar, especially in the matan ajrumiyah. The objectives of8 the research are to find out the difference between using the cooperative education model of the STAD Type and the method of 8translation rules in teaching grammar in the matan ajrumiyah to the student of h. Abdul karim syu’aib guguak randah . The researcher uses quantitative research with an exsperimental design and the researcher takes the research sample the pre test- post test control group., the research population is 200 students, and 32 s8tudents were sampled. The researcher uses the random sampling method, and the data analysis using the SPPS 20 progaram.As for the result of the research, there is difference and impact learning model in teaching ilmu nahwu using matan ajrumiyyah studebt of h. Abdul karim syu’aib guguak randah, so the hypothesis is rejected and the alternative hypothesis is accepted 4,37> 2,047. What is 8meant is there of cooperattive learning model of the STAD type in teaching ilmu nahwu in matan ajrumiyyah to the student of h. Abdul karim syu’aib guguak randah agam.